China’s Poverty Statistics. - Park, A; Wang, S (Elsevier, 2001)
China's official poverty statistics show a dramatic reduction in poverty from 31% of the rural population in 1978 to 3% in 2000. We evaluate possible sources of bias in these estimates and conclude that the official statistics underestimate rural poverty and overstate the speed of poverty reduction. Direct measures of nutritional outcomes support the contention that poverty is more widespread than suggested by official statistics. Priority should be given to constructing new statistics to accurately measure urban poverty. The method for calculating county income per capita, a key policy variable affecting official poor county designation, is ad hoc and subject to political influence.